The New Nitinol Conformable Self-Expandable Metal Stents for Malignant Colonic Obstruction: A Pilot Experience as Bridge to Surgery Treatment. (2nd January 2014) - Di Mitri, Roberto; Mocciaro, Filippo
Abstract : Introduction . Self-expandable metal stents (SEMS) are a nonsurgical option for treatment of malignant colorectal obstruction also as a bridge to surgery approach. The new nitinol conformable stent has improved clinical outcomes in these kinds of patients. We report a pilot experience with nitinol conformable SEMS placement as bridge to surgery treatment in patients with colorectal obstruction. Materials and Methods . Between April and August 2012, we collected data on colonic nitinol conformable SEMS placement in a cohort of consecutive symptomatic patients, with malignant colorectal obstruction, who were treated as a bridge to surgery. Technical success, clinical success, and adverse events were recorded. Results. Ten patients (7 male (70%)), with a mean age of 69.2 ± 10.1, were evaluated. The mean length of the stenosis was 3.6 ± 0.6 cm. Five patients (50%) were treated on an emergency basis. The median time from stent placement to surgery was 16 days (interquartile range 7–21). Technical and clinical success was achieved in all patients with a significant early improvement of symptoms. No adverse events due to the SEMS placement were observed. Conclusion . This pilot study confirmed the important role of nitinol conformable SEMS as a bridge to surgery option in the treatment of symptomatic malignant colorectal obstruction.